Analysis of Pedagogic Competency of Mathematical Education Students in Microteaching Course at the Universitas Sembilanbelas November Kolaka - Fitriyani Hali; Herlina Herlina (USN Kolaka, 2018)
One of the competencies that must be possessed by teachers or prospective teachers to become professional teachers is pedagogical competence. Pedagogic competence is the ability of a teacher to manage the learning process that relates to students. Therefore, pedagogical competence is very important for mathematics education students as prospective teachers. This study aims to determine the pedagogic competencies possessed by students, to know the strengths and weaknesses of students' pedagogical competencies, to identify the causes of weaknesses in students' pedagogical competencies, and determine alternative solutions to the weaknesses of students' pedagogical competencies. This research is a descriptive study with a qualitative approach. The subjects in this research are Mathematics Education Study Program students who took Microteaching courses. Data collection in this study was carried out through giving tests and interviews. Data was analyzed in quantitative and qualitative ways. The conclusion of the results of this study are 1) students' pedagogical competencies are in the low category; 2) The advantages of pedagogical competencies possessed by students are a) understanding the students' characteristics; b) mastering the concepts, principles, and procedures for developing curriculum or expertise programs; c) creating learning situations that are active, interactive, communicative, effective, and fun, as well as effective students guidance. While the weaknesses of pedagogic competence possessed by students are: a) mastering learning theory and learning principles; b) mastering theories, principles, and learning strategies; c) mastering the use of media, communication technology, and information, as well as reflective actions to improve the quality of learning; d) mastering concepts, principles, and learning assessment strategies; e) understanding the process and results and the impact of learning for students. 3) Factors that lead to the students' weak pedagogical competence are lack of students' motivation in improving and developing their pedagogical abilities and lack of tasks or exercises carried out by students in developing their pedagogical abilities, and lack of students' creativity in completing tasks. 4) Efforts that can be used as alternative solutions namely applying the Lesson Study approach and providing material reinforcement of pedagogic abilities.